Structural Intensity Simulation of Bolt Joints in Vibration Environment - Yongjuan Zhang; Guoying Zeng; Dengfeng Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The paper a nonlinear model of bolt joints structure in vibration environment is built, including the friction, contact and so on complex nonlinear factors. Structure Intensity (SI) of it is calculated by Finite Element Method（FEM）as an approach for the state identification of bolts joints structure in vibration environment. The plots of the structure intensity vector under different tightening torque were obtained and showed the SI changes of bolt joints structure with different tightening torque, and showed the energy distribution and transmission at different tightening torque.In order to compare, The SI maps of of rigid connected beam at different tightening torque also were obtained.